1995
DOI: 10.1016/1044-0305(95)00053-g
|View full text |Cite
|
Sign up to set email alerts
|

False positives and the detection of cyclodextrin inclusion complexes by electrospray mass spectrometry

Abstract: The results of previous works that have claimed to detect cyclodextrin inclusion complexes via the "soft" ionization technique of electrospray ionization mass spectrometry are revisited. A more extensive study of cyclodextrin mixtures with amino acids and small peptides demonstrates that amino acid and peptide "complexes" are detected by electrospray mass spectrometry regardless of the presence (or not) of an aromatic moiety on the side chain. Amino acids that may be least likely to form hydrophobic inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
108
0
4

Year Published

1996
1996
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 14 publications
(6 reference statements)
6
108
0
4
Order By: Relevance
“…Ammonium ion, present as an impurity in reagent grade methanol [54] competed with the uptake of Li, and for this reason, the hydroxide salts of Li, Na, and K were used for several of the metal ion uptake experiments, otherwise, the reagent grade chloride salts of Na, K, Rb, and Cs were used. A minimum mole ratio of total metal ion to PEG was set at 10:1 to ensure the starting solution was under thermodynamic conditions [13] to minimize kinetic [55] and/or solute clustering [56,57] contributions to the sampled ion population. The sample preparation procedure was simply to dissolve the salts with a minimum of distilled deionized water, and then diluting with reagent grade methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Ammonium ion, present as an impurity in reagent grade methanol [54] competed with the uptake of Li, and for this reason, the hydroxide salts of Li, Na, and K were used for several of the metal ion uptake experiments, otherwise, the reagent grade chloride salts of Na, K, Rb, and Cs were used. A minimum mole ratio of total metal ion to PEG was set at 10:1 to ensure the starting solution was under thermodynamic conditions [13] to minimize kinetic [55] and/or solute clustering [56,57] contributions to the sampled ion population. The sample preparation procedure was simply to dissolve the salts with a minimum of distilled deionized water, and then diluting with reagent grade methanol.…”
Section: Methodsmentioning
confidence: 99%
“…In all these studies, the aromatic guest molecules were bearing at least one polar group. However, Cunniff and Vouros [18] have reported that ES-MS on complexes with non-aromatic amines gave false positives. Conversely, ES-MS on ␤-CD complexes with aromatic non-polar molecules resulted in false negatives.…”
mentioning
confidence: 99%
“…However, extensive dissociation during ESI is also observed for some electrostatically stabilized complexes, even under the most gentle ionization conditions [34]. ESI-MS can also produce false-positive results, i.e., some analytes tend to form noncovalent gas-phase assemblies during ESI, despite the nonexistence of the corresponding complexes in solution [35,36]. Hu et al have demonstrated that the nonspecific binding of metal ions to proteins can be a severe problem when the ionization conditions are not chosen properly [37].…”
mentioning
confidence: 99%